The International Health Cooperation Agencies: The COVAX case - Hernández Torres, Francisca Angélica (Interdisciplinary Journal of Epidemiology and Public Health, 2023)
International Health Cooperation is defined as collaboration between countries as well as different international organizations, seeking to contribute to improving global health conditions in low- and middle-income countries. Different International Health Cooperation agencies have gradually gained momentum, mainly Civil Society Organizations, which has led, on several occasions, to go from pursuing the objectives of the countries that receive support to pursuing the objectives of the grantees, in In this report, a review of the International Health Cooperation is made in light of the COVID 19 pandemic, specifically the COVAX case.